THE SECRET EXPLORERS AND THE SMOKING VOLCANO - King, SJ; O'Shea, Ellie (New York, New York : DK Publishing, 2021)
Learn all about volcanoes in this explosive sixth adventure with The Secret Explorers. This group of brilliant kids come together from all four corners of the globe to fix problems, solve mysteries and gather knowledge all over the planet - and beyond. Whenever their help is needed, a special sign will appear on a door. They step through to the Exploration Station, and receive their mission... In this instalment, volcanoes expert Cheng and biology expert Leah experience the thrill and danger of a volcanic eruption up close. Cheng is beyond excited to finally be witnessing the real life volcano, Mount Yasur, in action, but the Secret Explorers soon realise that some of their new friends are missing! It's up to them to rescue their friend and his dog and get them off the volcano before it erupts again, in an even bigger explosion than before. From surfing down a volcano, to daring helicopter rescues, Cheng and Leah need to use all their skills and knowledge to succeed in their mission... Packed with fun facts about volcanic eruptions, this thrilling adventure is perfect for young readers.
Includes quiz and answers.
Keywords: Volcanoes -- Juvenile fiction; Rescues -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Vanuatu -- Juvenile fiction; Action and adventure fiction; Detective and mystery fiction